1998
DOI: 10.1093/ps/77.11.1646
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disturbances in male broilers of different strains. 1. Performance, mortality, and right ventricular hypertrophy

Abstract: Two trials were carried out to test the susceptibility for metabolic disturbances of different strains of male broilers. In Trial 1, 1,890 male chickens were allotted in a randomized block design with seven treatments (Arbor Acres, Avian Farms, Cobb-500, Hubbard-Peterson, ISA, Naked Neck, and Ross) and six blocks of 45 chickens. Trial 2 involved 2,184 male chickens of six strains (Arbor Acres, Avian Farms, Cobb 500, Hubbard-Peterson, ISA Naked Neck, and Ross) allotted in seven complete blocks of 52 birds. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 11 publications
3
17
0
7
Order By: Relevance
“…The improved body weight gain of this strain, possibly due to higher feed intake and several other factors might be involved herewith. Our results are in agreement with the reports of several other previous researchers (Gonzales et al, 1998;Sarker et al, 2001Sarker et al, & 2002Abdullah et al, 2010), who found similar variations in rearing different strains under experimental conditions. The differences of the live weight and weight gain of the broiler strains may be explained by different factors, for example, genotype, feed, sex, strains, environmental conditions, climatic effects and so on.…”
Section: Discussion Growth Performance (Live Weight and Live Weight supporting
confidence: 94%
See 1 more Smart Citation
“…The improved body weight gain of this strain, possibly due to higher feed intake and several other factors might be involved herewith. Our results are in agreement with the reports of several other previous researchers (Gonzales et al, 1998;Sarker et al, 2001Sarker et al, & 2002Abdullah et al, 2010), who found similar variations in rearing different strains under experimental conditions. The differences of the live weight and weight gain of the broiler strains may be explained by different factors, for example, genotype, feed, sex, strains, environmental conditions, climatic effects and so on.…”
Section: Discussion Growth Performance (Live Weight and Live Weight supporting
confidence: 94%
“…The differences of the live weight and weight gain of the broiler strains may be explained by different factors, for example, genotype, feed, sex, strains, environmental conditions, climatic effects and so on. Gonzales et al (1998) found strain effects among several strains of birds in live weight. Korver et al (2004) reported that genotype may affect the body weight of different broiler strains.…”
Section: Discussion Growth Performance (Live Weight and Live Weight mentioning
confidence: 97%
“…Segundo Havenstein et al (2003), de 1957 a 2001, o melhoramento genético foi responsável por 85% da evolução no desempenho de frangos de corte. Em conseqüência disso, trabalhos que avaliem linhagens são muito importantes pelo valor que o melhoramento genético tem no desenvolvimento da avicultura e em função da rapidez com que as mudanças ocorrem nesse segmento da avicultura.…”
Section: Introductionunclassified
“…Several studies have attempted to relate broiler chicken susceptibility to ascites after hatching to anatomical or physiological parameters like right ventricle:total ventricle weight, hematocrit, thyroid hormones, and blood viscosity (Maxwell et al, 1986;Julian, 1987;Silversides et al, 1997;Gonzales et al, 1998;Nir, 1998); however, there is no report in the literature showing if in neonatal chicks these parameters are related to breeder age. Thus, the objective of this study was to investigate how breeder age (30, 45 and 60 weeks) affects eggshell characteristics and blood, cardiac and lung parameters of neonatal chicks.…”
Section: Introductionmentioning
confidence: 99%